Greenwashing in Twin Date Promotions: An Analysis of Brand Communication Strategies - Fismayatni Cholifah; Usep Suhud; Mohammad Rizan (Greenation International Journal of Economics and Accounting, 2025)
This study aims to examine the presence and characteristics of greenwashing in brand communication strategies during e-commerce promotional events known as twin dates (e.g., 10.10, 11.11, 12.12). It also explores how consumers perceive environmental claims made by brands during these campaigns. Design/methodology/approach---Using a descriptive qualitative approach, the study conducts content analysis on 15 promotional visuals and texts collected from Shopee and Tokopedia during the 2023 twin date campaigns. The analysis focuses on identifying visual cues, eco-labels, and sustainability-related terms that may be misleading. Findings, the findings show that many brands use green visuals, eco-friendly labels, and sustainability language without credible verification or certification. This practice leads to increased consumer scepticism, especially among environmentally conscious users, and may negatively impact long-term brand trust. Research limitations/implications, the study is limited to two e-commerce platforms and one promotional period. Future research could explore cross-platform or cross-country comparisons and integrate quantitative consumer response analysis. Practical implications---this research provides valuable insights for marketers, digital platforms, and regulators to identify greenwashing practices and develop more ethical, evidence-based communication strategies that promote sustainable consumption.